2005
DOI: 10.1042/bj20040475
|View full text |Cite
|
Sign up to set email alerts
|

Inositol phosphoceramide synthase is a regulator of intracellular levels of diacylglycerol and ceramide during the G1 to S transition in Saccharomyces cerevisiae

Abstract: We recently reported that DAG (diacylglycerol) generated during sphingomyelin synthesis plays an important role in protein kinase C activation and cell proliferation in Madin-Darby canine kidney cells [Cerbon and Lopez-Sanchez (2003) Biochem. J. 373, 917-924]. In yeast cells, IPC (inositol phosphoceramide) synthase catalyses the transfer of phosphoinositol from phosphatidylinositol to ceramide to form IPC and generates DAG. In the present study, we found that, during the G1 to S transition after N2-starvation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Studies of both yeast and mammalian cells have shown that ongoing sphingolipid synthesis is essential for cell proliferation (14). However, recent work with the kinetoplastid parasite Leishmania demonstrate that log-phase promastigote- 456 SUTTERWALA ET AL.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of both yeast and mammalian cells have shown that ongoing sphingolipid synthesis is essential for cell proliferation (14). However, recent work with the kinetoplastid parasite Leishmania demonstrate that log-phase promastigote- 456 SUTTERWALA ET AL.…”
Section: Resultsmentioning
confidence: 99%
“…This concept is supported by the literature, which indicates that sphingolipid metabolism represents a highly interconnected network. In previous studies, treatment with aureobasidin A, which inhibits the IPC synthase Aur1p (38), increased ceramides while reducing levels of diacylglycerol, the other product of the IPC synthesis reaction (23). Furthermore, the addition of inositol to the culture medium markedly increased cellular PtdIns (39), resulting in increased complex sphingolipid synthesis with concomitant decreases in ceramides (22).…”
Section: Inhibition Of Ipc Synthase Ameliorates Reduction In Sphingoidmentioning
confidence: 99%
“…The addition of inositol to the culture media decreased ceramide levels as IPC and, it was inferred, PtdIns increased (22); however, these effects have not been demonstrated in cells with perturbed PtdIns metabolic pathways. Furthermore, it has also been shown that inhibition of IPC synthesis increased the immediate metabolic precursor, ceramides (23), but the effect on other sphingolipids, including signaling sphingolipids, remains unclear. Together, these results raise tantalizing possibilities about the potential for turnover between PtdIns(4)P and PtdIns to regulate sphingolipid synthesis through nonsignaling mechanisms.…”
mentioning
confidence: 99%
“…In mammalian cells, SM production is similarly coupled to conversion of phosphatidylcholine (PC) to DAG. Thus, glycerolipid sensors such as the DAG-binding domain in protein kinase C could provide a mechanism to monitor the rate of sphingolipid biosynthesis (Cerbon and del Carmen Lopez-Sanchez 2003;Cerbon et al 2005).…”
Section: Sphingolipid Homeostasis In the Er And Beyondmentioning
confidence: 99%